Pengaruh Likuiditas, Solvabilitas, Profitabilitas terhadap Nilai Perusahaan Sektor Perkebunan yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2024 - Jani Puspita Sari; Hamonangan Siallagan; Mei Hotma Mariati Munte (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
This study aims to examine the effects of liquidity (Current Ratio), solvency (Debt to Equity Ratio), and profitability (Return on Asset) on firm value (Tobin’s Q) across 22 plantation sector issuers listed on the Indonesia Stock Exchange during the 2021–2024 period. Employing a quantitative approach and saturated sampling yielding 88 total observations, panel data analysis was executed using EViews 12 based on the Random Effect Model selection. The empirical findings reveal that liquidity and solvency exert no significant partial effect with a negative direction on firm value, recording respective probability values of 0.7539 and 0.7400. Conversely, profitability proves to exert a positive and highly significant effect on firm value with a probability of 0.0000 and a t-statistic of 10.50256. These findings confirm that asset returns serve as the primary determinant governing corporate value among investors.